Hf Doping Boosts the Excellent Activity and Durability of Fe-N-C Catalysts for Oxygen Reduction Reaction and Li-O2 Batteries - Mingrui Liu; Shaoqiu Ke; Chuangqing Sun; Chenzhuo Zhang; Shijun Liao (Nanomaterials)
Developing highly active and durable non-noble metal catalysts is crucial for energy conversion and storage, especially for proton exchange membrane fuel cells (PEMFCs) and lithium-oxygen (Li-O2) batteries. Non-noble metal catalysts are considered the greatest potential candidates to replace noble metal catalysts in PEMFCs and Li-O2 batteries. Herein, we propose a novel type of non-noble metal catalyst (Fe-Hf/N/C) doped with Hf into a mesoporous carbon material derived from Hf-ZIF-8 and co-doping with Fe and N, which greatly enhanced the activity and durability of the catalyst. When applied in the cathode of PEMFCs, the current density can reach up 1.1 and 1.7 A cm−2 at 0.7 and 0.6 V, respectively, with a maximum power density of 1.15 W cm−2. The discharge capacity of the Li-O2 batteries is up to 15,081 mAh g−1 with Fe-Hf/N/C in the cathode, which also shows a lower charge overpotential, 200 mV lower than that of the Fe/N/C. Additionally, the Fe-Hf/N/C catalyst has demonstrated better stability in both PEMFCs and Li-O2 batteries. This reveals that Hf can not only optimize the electronic structure of iron sites and increase the active sites for the oxygen reduction reaction, but can also anchor the active sites, enhancing the durability of the catalyst. This study provides a new strategy for the development of high-performance and durable catalysts for PEMFCs and Li-O2 batteries.